1994
DOI: 10.1111/j.1365-2559.1994.tb00533.x
|View full text |Cite
|
Sign up to set email alerts
|

The anaplastic variant of centrocytic lymphoma is marked by frequent rearrangements of the bcl‐1 gene and high proliferation indices

Abstract: Ten cases of classic centrocytic lymphoma as defined in the Kiel classification system were investigated for their immunophenotype, their proliferation activity and by means of molecular diagnostics. The findings were compared to those obtained from a group of nine cases of anaplastic centrocytic lymphoma. Both groups showed virtually identical immunohistochemical characteristics with positivity for CD5 and negativity for CD10 and CD23. In the group of anaplastic centrocytic lymphoma, there were considerably h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 18 publications
(1 reference statement)
2
32
1
Order By: Relevance
“…Cytology Classical + small cell versus blastic + pleo + variants to show high indices (Lardelli et al, 1990;Ott et al, 1994Ott et al, , 1997Jares et al, 1996;Campo et al, 1999). The present, extensive study of various prospective trials confirmed these data.…”
Section: Characteristicssupporting
confidence: 70%
“…Cytology Classical + small cell versus blastic + pleo + variants to show high indices (Lardelli et al, 1990;Ott et al, 1994Ott et al, , 1997Jares et al, 1996;Campo et al, 1999). The present, extensive study of various prospective trials confirmed these data.…”
Section: Characteristicssupporting
confidence: 70%
“…Although the features of blastic or large cell MCL (22)(23)(24) and peripheralizing MCL (13,(25)(26)(27)(28) have each been well described in the literature, cases of blastic MCL presenting with predominant blood and marrow involvement have not been clearly identified to our knowledge. Two previous reports describe primarily leukemic disorders with some similarities to the current patient series presented here.…”
Section: Discussionmentioning
confidence: 97%
“…This translocation has been reported to involve the juxtaposition of the bcl-l gene at 11 q 13 with the immunoglobulin heavy chain gene at 14q32 and results in deregulation of cyclin D1/PRAD1. [5][6][7] We found the t( 11; 14) in 2 of 4 patients. When confronted with a peripheral blood smear containing blast-like cells, the differential diagnosis is broad and includes acute leukemias, chronic lymphoproliferative disorders, and other types of peripheralized lymphoma.…”
Section: Discussionmentioning
confidence: 99%